2013
DOI: 10.1111/opo.12029
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glaucoma referral refinement criteria on referral to, and first‐visit discharge rates from, the hospital eye service: the Health Innovation & Education Cluster (HIEC) Glaucoma Pathways project

Abstract: The results support that referrals for a raised IOP alone or in combination with an abnormal VF be classified as low-risk and undergo referral refinement. Adherence to the JCG and the NICE commissioning guidance as onward referral criteria for specialist optometrists in this referral refinement scheme would result in fewer referrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 15 publications
0
39
1
Order By: Relevance
“…Compared with Ratnarajan et al ’s study, abnormal optic disc as a reason for referral contributed to one of the lowest rates for discharges of 19% 4. In part, this is a consequence of our lower rates of discharge for other types of referral (particularly raised IOP).…”
Section: Discussioncontrasting
confidence: 59%
“…Compared with Ratnarajan et al ’s study, abnormal optic disc as a reason for referral contributed to one of the lowest rates for discharges of 19% 4. In part, this is a consequence of our lower rates of discharge for other types of referral (particularly raised IOP).…”
Section: Discussioncontrasting
confidence: 59%
“…Some patients were identified as having narrow angles by an OSI, whereas the original referral had not mentioned this (otherwise the patient would have met the exclusion criteria for the scheme). In a previous study, 20% of patients referred on the basis of elevated IOP were found to have another abnormality, such as narrow anterior chamber angles . Only 7% of optometrists stated that they would include details in a referral letter of anterior chamber depth …”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, 20% of patients referred on the basis of elevated IOP were found to have another abnormality, such as narrow anterior chamber angles. 21 Only 7% of optometrists stated that they would include details in a referral letter of anterior chamber depth. 22 This study demonstrates that gonioscopic evaluation needs further refinement.…”
Section: Discussionmentioning
confidence: 99%
“…High‐quality eye care involves optometrists and ophthalmologists working together with general practitioners ( GPs ), orthoptists and allied health care workers or professionals working for organisations providing low vision rehabilitation ( LVR ) and support services . In A ustralia, this part of the health‐care system is under substantial pressure due to the growing number of people with chronic eye disease, such as age‐related macular degeneration ( AMD ), diabetic retinopathy ( DR ) and glaucoma (GL) .…”
mentioning
confidence: 99%